KOMPARASI PENENTUAN LOKASI GANGGUAN ANTARA FAULT LOCATOR DAN RELE JARAK PADA PENGHANTAR 150 KV TELUK KUANTAN-RENGAT - Arifin, Jamal; Yamashika, Herris; Dwiharzandis, Aggrivina (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2026)
Transmission system reliability is an essential factor in maintaining continuous power supply. Accurate and fast fault location identification is necessary to shorten repair time. This study compares two fault location determination methods, namely the Fault Locator based on Traveling Wave Signal (TWS) and the Distance Relay based on impedance on the 150 kV Teluk Kuantan–Rengat transmission line. The results show that the TWS method has a smaller error rate compared to the impedance method. The average error using TWS is 0.42%, while the impedance method shows 1.86%. Thus, the TWS method is more accurate and recommended for use in 150 kV transmission systems.Keywords: fault locator, traveling wave, distance relay, transmission system, fault location